Support Structures and Activities for Teachers Preparing for Game-Based Learning (International Conference on Computers in Education, 2022)
In this paper, we share the experience of teacher preparation for game-based learning by describing a series of technical, pedagogical, and content support activities that helped teachers design and implement Minecraft-based modules in their classes. The teachers made use of the WhatIf Hypothetical Implementations in Minecraft (WHIMC), a set of Minecraft worlds that students can explore to learn more about astronomy, geosciences, and ecology. Technical support included setting up of the WHIMC server and Minecraft accounts for teachers and students, and teacher support familiarization of the WHIMC worlds. Pedagogical support included module reviews and a dry run that allowed teachers to refine their learning modules. Content support included assisting teachers with ensuring alignment between curricular goals and WHIMC functions and features. These support activities helped teachers achieve some success in their module implementations. Additional opportunities for improvement include a separate hands-on orientation session for students and peer observation to disseminate novel pedagogical strategies. Overall, this paper illustrates how teachers need to be supported in order to prepare and deploy a game-based learning module successfully.